Study of Effect of Seal Profile on Tribological Characteristics of Reciprocating Hydraulic Seals - S. Bhaumik; A. Kumaraswamy; S. Guruprasad; P. Bhandari (Tribology in Industry, 2015)
Effect of seal profile on tribological characteristics such as leakage, friction, and wear in reciprocating hydraulic seals was predicted as a function of number of parameters such as rod velocity, sealed pressure and surface roughness. Experiments were conducted on a specially designed test rig at rod velocities ranging from 0.12-0.5 m/s, oil pressures from 1-20 MPa and rod average surface roughness value from 0.2-0.4 µm. Theoretical analysis was carried out using Greenwood Williamson (GW) model for determining leakage, friction and Archard’s equation for evaluating wear in rectangular and U-cup seal profiles. Comparison of theoretically estimated data with experimental results for two seal profiles revealed good agreement. Unlike rectangular seal, back pumping of the fluid was observed in case of U-cup seal. It was also observed that, the performance of U-cup seal profile in terms of leakage, friction and wear was relatively better compared to rectangular seal profile under given set of test parameters.